Policy Mapping for Direction on Green Vertical Housing Development in Indonesia - Larasati, Dewi; Wilis, Furry Andini; Dewi Nurhayati; Roiswahid Dimas Pangestu; Allis Nurdini; Arnott Ferels (Nakhara : Journal of Environmental Design and Planning, 2025)
Indonesia’s rapid urbanization has accelerated the construction of vertical public housing as a state-led response to growing urban housing needs. Compared to the general housing sector, these projects hold strategic importance due to their large scale, policy alignment, and reliance on public financing. However, this expansion intensifies resource consumption and environmental degradation, particularly in the absence of mandatory green building (GB) standards. Although GB initiatives have been introduced across multiple sectors, their fragmented implementation and weak enforcement diminish their overall effectiveness. Vertical public housing, therefore, presents a key opportunity for policy innovation, where governmental authority can effectively institutionalize sustainability practices. This study aims to map existing GB-related regulations and develop strategic policy directions for sustainable vertical housing in Indonesia. The research adopts a four-stage framework: (1) a systematic review of 50 Scopus-indexed articles (1985–2023) to identify key aspects of GB policy, (2) regulatory mapping of 36 official documents analyzed chronologically to capture policy evolution and thematic coverage, (3) a comparative policy review involving six countries to extract relevant lessons, and (4) synthesis of results into actionable policy directions and strategies tailored to Indonesia’s vertical housing context. Findings highlight four priorities: enhancing stakeholder engagement and awareness; integrating technical standards and performance assessments; enforcing GB compliance for buildings over 5,000 square meters, and establishing financial and non-financial incentives. The resulting framework promotes stronger coordination, regulatory clarity, and practical enforcement. Ultimately, this study contributes to advancing coherent, context-specific green policies that support Indonesia’s transition toward sustainable and resilient urban housing.